A role for triglyceride lipase brummer in the regulation of sex differences in Drosophila fat storage and breakdown - Wat, Lianna W.; Chao, Charlotte; Bartlett, Rachael; Buchanan, Justin L.; Millington, Jason W.; Chih, Hui Ju; Chowdhury, Zahid S.; Biswas, Puja; Huang, Vivian; Shin, Leah J.; Wang, Lin Chuan; Gauthier, Marie-Pierre L.; et al. (PLoS biology, 2020)
Triglycerides are the major form of stored fat in all animals. One important determinant of whole-body fat storage is whether an animal is male or female. Here, we use Drosophila , an established model for studies on triglyceride metabolism, to gain insight into the genes and physiological mechanisms that contribute to sex differences in fat storage. Our analysis of triglyceride storage and breakdown in both sexes identified a role for triglyceride lipase brummer ( bmm ) in the regulation of sex differences in triglyceride homeostasis. Normally, male flies have higher levels of bmm mRNA both under normal culture conditions and in response to starvation, a lipolytic stimulus. We find that loss of bmm largely eliminates the sex difference in triglyceride storage and abolishes the sex difference in triglyceride breakdown via strongly male-biased effects. Although we show that bmm function in the fat body affects whole-body triglyceride levels in both sexes, in males, we identify an additional role for bmm function in the somatic cells of the gonad and in neurons in the regulation of whole-body triglyceride homeostasis. Furthermore, we demonstrate that lipid droplets are normally present in both the somatic cells of the male gonad and in neurons, revealing a previously unrecognized role for bmm function, and possibly lipid droplets, in these cell types in the regulation of whole-body triglyceride homeostasis. Taken together, our data reveal a role for bmm function in the somatic cells of the gonad and in neurons in the regulation of male–female differences in fat storage and breakdown and identify bmm as a link between the regulation of triglyceride homeostasis and biological sex.